2017
DOI: 10.1111/neup.12408
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution melting and immunohistochemical analysis efficiently detects mutually exclusive genetic alterations of adamantinomatous and papillary craniopharyngiomas

Abstract: Craniopharyngioma consists of adamantinomatous and papillary subtypes. Recent genetic analysis has demonstrated that the two subtypes are different, not only in clinicopathological features, but also in molecular oncogenesis. Papillary craniopharyngioma (pCP) is characterized by a BRAF mutation, the V600E (Val 600 Glu) mutation. Adamantinomatous craniopharyngioma (aCP) can be distinguished by frequent β-catenin gene (CTNNB1) mutations. Although these genetic alterations can be a diagnostic molecular marker, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
(120 reference statements)
0
7
0
Order By: Relevance
“…11,12 Several recent studies have shown that CTNNB1 and BRAF (V600E) mutations were mutually exclusive for ACP and PCP tumors. 13,14 In the majority of ACP tumors, somatic mutations in exon 3 of CTNNB1 prevents degradation of β-catenin protein, thus activating the Wnt signaling, 15,16 whereas mutations in BRAF exon 15 in PCP tumors lead to MAP kinase pathway activation. 17 This discovery of specific mutations became useful to distinguish between ACP and PCP, and leading to the development of novel targeted therapies for patients with BRAF mutations in PCP cases.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Several recent studies have shown that CTNNB1 and BRAF (V600E) mutations were mutually exclusive for ACP and PCP tumors. 13,14 In the majority of ACP tumors, somatic mutations in exon 3 of CTNNB1 prevents degradation of β-catenin protein, thus activating the Wnt signaling, 15,16 whereas mutations in BRAF exon 15 in PCP tumors lead to MAP kinase pathway activation. 17 This discovery of specific mutations became useful to distinguish between ACP and PCP, and leading to the development of novel targeted therapies for patients with BRAF mutations in PCP cases.…”
Section: Introductionmentioning
confidence: 99%
“…Adamantinomatous craniopharyngiomas (adaCP), a subtype of rare epithelial tumors, craniopharyngiomas, accounts for 5.6% to 15% of intracranial tumors and occurs in both children and young people . Although the histopathological classification of adaCP was considered as benign epithelial tumor, due to the complicated and important anatomical relationships around the tumor (such as optic nerve, optic chiasma, pituitary stalk, internal carotid artery, anterior cerebral artery, middle cerebral artery and other arteriae perforantes, the pituitary gland, hypothalamus, etc) and the factors of tumor own (such as parts, calcification, extent, adhesion, etc), total surgical excision rate of adaCP is low, the incidence of postoperative complications is high and serious, mortality, and disability rate are difficult to control .…”
Section: Introductionmentioning
confidence: 99%
“…Molecular detection of BRAF V600E mutation cannot yet be achieved in the prescribed time for intraoperative consultation (20-30 minutes). Rapid direct immunohistochemical methods are feasible but no study has tested the BRAF V600E antibody in the setting of craniopharyngioma intraoperative diagnosis (37)(38)(39). Figure 4 reports an algorithm proposed for intraoperative decision making.…”
Section: Discussionmentioning
confidence: 99%